2022
DOI: 10.3390/jmse10020217
|View full text |Cite
|
Sign up to set email alerts
|

Seaport Terminals Risks Prioritization Using a Structural Modeling-Based Approach: A Real Case Study

Abstract: Port risk management (PRM) during port operations is a current problem that can negatively affect the environment, people, and economic issues. In the literature, there is an enormous amount of research related to supply chain risk management (SCRM) in various areas and with various objectives. However, PRM has not received the same degree of attention. In fact, port terminals are crucial links in most supply chain networks and an important pillar of international trade. Therefore, for better risk mitigation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The highest weights are assigned to factors such as 'natural disasters' and industrial accidents, indicating their significant impact on port safety and operational continuity. This prioritization aligns with previous studies that emphasize the vulnerability of ports to extreme weather events and human-induced hazards [59][60][61][62]. While novel hybrid prediction models have been presented in recent scientific research [63], the proposed model in this study produced reliable results.…”
Section: Discussionsupporting
confidence: 83%
“…The highest weights are assigned to factors such as 'natural disasters' and industrial accidents, indicating their significant impact on port safety and operational continuity. This prioritization aligns with previous studies that emphasize the vulnerability of ports to extreme weather events and human-induced hazards [59][60][61][62]. While novel hybrid prediction models have been presented in recent scientific research [63], the proposed model in this study produced reliable results.…”
Section: Discussionsupporting
confidence: 83%
“…For example, Fan et al [25] concluded that human factors are the main cause of maritime accidents; Budiyanto et al [17] believed that human factors, especially due to human work negligence in operating vehicle equipment, are one of the most important factors causing accidents in terminal container operations; Zhang et al [28] found that human factors are the primary influencing factors in port ship pilotage accidents, and discussed their impact on accident risks by studying the coupling effects between the human organizational factors and system factors. Furthermore, port workers' ability to apply new technologies, work operations, and safety awareness is closely related to professional training and safety education, indicating that management variables are also a major source of dangerous human behavior [27,29,30]. Next, facilities and equipment are critical materials for ensuring the smooth operation of ports.…”
Section: Internal Risk Factors Of the Port Logisticsmentioning
confidence: 99%
“…Moreover, the port management organization system is also a crucial component of the port logistics system. It has been suggested that proper organizational management is a significant element in maintaining the order of the port and guaranteeing the continuity of the system due to the complex environment of the port system and the closely related activities of each link; otherwise, it will cause problems such as congestion and even collision and conflict [4,10,30].…”
Section: Internal Risk Factors Of the Port Logisticsmentioning
confidence: 99%